Impact of Rehabilitation on Outcomes in Patients With Ischemic Stroke: A Nationwide Retrospective Cohort Study in Japan. Issue 3 (March 2017) - Yagi, Maiko; Yasunaga, Hideo; Matsui, Hiroki; Morita, Kojiro; Fushimi, Kiyohide; Fujimoto, Masashi; Koyama, Teruyuki; Fujitani, Junko
Abstract : Background and Purpose—: We aimed to examine the concurrent effects of timing and intensity of rehabilitation on improving activities of daily living (ADL) among patients with ischemic stroke. Methods—: Using the Japanese Diagnosis Procedure Combination inpatient database, we retrospectively analyzed consecutive patients with ischemic stroke at admission who received rehabilitation (n=100 719) from April 2012 to March 2014. Early rehabilitation was defined as that starting within 3 days after admission. The average rehabilitation intensity per day was calculated as the total units of rehabilitation during hospitalization divided by the length of hospital stay. A multivariable logistic regression analysis with multiple imputation and an instrumental variable analysis were performed to examine the association of early and intensive rehabilitation with the proportion of improved ADL score. Results—: The proportion of improved ADL score was higher in the early and intensive rehabilitation group. The multivariable logistic regression analysis showed that significant improvements in ADL were observed for early rehabilitation (odds ratio: 1.08; 95% confidence interval: 1.04–1.13; P <0.01) and intensive rehabilitation of >5.0 U/d (odds ratio: 1.87; 95% confidence interval: 1.69–2.07; P <0.01). The instrumental variable analysis showed that an increased proportion of improved ADL was associated with early rehabilitation (risk difference: 2.8%; 95% confidence interval: 2.0–3.4%; P <0.001) and intensive rehabilitation (risk difference: 5.6%; 95% confidence interval: 4.6–6.6%; P <0.001). Conclusions—: The present results suggested that early and intensive rehabilitation improved ADL during hospitalization in patients with ischemic stroke. Abstract : Supplemental Digital Content is available in the text.